Linking nutrition and sexual selection across life stages in a model butterfly system. (29th October 2012) - Tigreros, Natasha
Summary: Early nutrition plays an important role in determining adult fitness. Theory proposes that in organisms with complex life cycles, the fitness effects of larval nutritional constraints are mainly captured by two developmental traits: time and size at metamorphosis. However, recent evidence suggests that latent effects, which are independent of these developmental traits, must be included to fully understand how larval nutrition impacts fitness. In this study, I used the cabbage butterfly ( Pieris rapae ) as a model system to investigate how larval nutrition influences male fitness through development time, adult size and latent effects. Specifically, I examined how variation in dietary nitrogen impacts male fitness by measuring a comprehensive suite of pre‐ and postcopulatory traits. Results indicate a complex role for larval nutrition in determining adult fitness. Larval nutritional constraints influence adult fitness through three different pathways: development time, adult size and latent effects. Longer development times were associated with shorter adult life span and reduced male mating success. Body size was positively correlated with traits related to postcopulatory fitness, such as spermatophore size and protein content. Larval nitrogen availability, independent of the developmental traits, also affected traits associated with male mating success such as wing coloration and latency to first mating. These results provide new insights into how larval nitrogen availability alters adult fitness by revealing novel links between larval dietary nitrogen and various adult fitness components. Abstract : Abstract : Lay Summary